The impact of table tennis intervention on short video addiction among college students in China: the chained mediation effect of cognitive bias and self-control - Wang, Kanglin; Sun, Jian; Han, Jiangtao; Wu, Zaihao (Frontiers in Psychology, 2025)
BackgroundThis study focuses on the impact of a 16-week table tennis exercise intervention on college students’ short video addiction and explores the chain mediating mechanism of cognitive bias and self-control therein. Currently, the short video addiction rate among college students is high, and physical exercise has shown unique value in digital addiction intervention. Still, the cognitive-behavioral level of the action path is not yet clear.MethodsSixty college students with short video addiction (daily average usage duration ≥ 4 h) from a certain university in Chengdu, China, were selected and randomly divided into an experimental group (30 people) and a control group (30 people). The experimental group implemented a 16-week, 3-times-a-week moderate-intensity table tennis intervention (60–80% of the maximum heart rate), while the control group maintained regular activities. The Short Video Addiction Scale for College Students (SVAS), Negative Cognitive Processing Bias Questionnaire, and Self-Control Scale were used for pre- and post-tests. Repeated-measures analysis of variance and the Hayes Process plugin (Model 6) were used to test the mediating effect.ResultsThe table tennis intervention significantly reduced the short video addiction level and cognitive bias and improved self-control ability in the experimental group. The improvement was significantly better than that in the control group. Cognitive bias and self-control formed a chain mediating path, and the total indirect effect accounted for 68.33% of the total effect.ConclusionTable tennis exercise can inhibit college students’ short video addiction through the chain mediating mechanism of reducing cognitive bias and enhancing self-control, providing an empirical basis from the perspective of sports psychology for digital addiction intervention.